Hardware and Software: Verification and Testing 6th International Haifa Verification Conference, HVC 2010, Haifa, Israel, October 4-7, 2010. Revised Selected Papers - Barner, Sharon; Harris, Ian.; Kroening, Daniel; Raz, Orna.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th International Haifa Verification Conference, HVC 2010, held in Haifa, Israel in October 2010. The 10 revised full papers presented together with 7 invited papers were carefully reviewed and selected from 30 submissions. The papers address all current issues, challenges and future directions of verification for hardware, software, and hybrid systems and have a research focus on hybrid methods and the migration of methods and ideas between hardware and software, static and dynamic analysis, pre- and post-silicon.
Keywords: Computer science; Software engineering; Logic design; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters